Place of international treaties in the system of sources of international private law - Miashchanava, Maryia V. (Journal of the Belarusian State University. Law, 2020)
The author analyses the issues of recognition of international treaties as an independent source of private international law, the procedure for applying the provisions of international treaties within the legal framework of the Republic of Belarus. Attention is focused on amendments in the Belarusian legislation, which retained the general implementing rule on the direct application of the provisions of international treaties by the subjects of national law, but excluded the recognition of international treaties as an integral part of the law of the Republic of Belarus. The position of the Constitutional Court of the Republic of Belarus on this problem is considered. It is proposed to call the process of «incorporation» of the rules of international treaties into national law «implementation», since this term is the broadest and includes both the transformation of the provisions of international treaties into domestic law and the direct application of the latter on the basis of a general implementing rule.
Keywords: implementation; incorporation; private international law; general implementing rule; reception; transformation